Widespread ingestion of lead pellets by wild chukars in Northwestern Utah - Richard J. Bingham; Randy T. Larsen; John A. Bissonette; Jeffery O. Hall (Wildlife Society Bulletin)
ABSTRACT The use of lead ammunition has generated much debate because lead is toxic and elevated lead exposure is documented in >130 wildlife species. We expanded on prior reports of ingested lead in chukars (Alectoris chukar) to assess lead exposure at greater spatial and temporal extents. Our specific objectives concerning lead exposure in chukars from northwestern Utah, USA (approx. 49,000 km2) were to: 1) approximate a threshold for background versus elevated lead exposure; 2) investigate spatial and temporal variation of lead exposure; and 3) assess the utility of combining frequencies of ingested gizzard lead and elevated liver lead to estimate lead ingestion rates. We obtained hunter and volunteer‐harvested chukars collected during July–January, 2003–2011. Using liver lead residues from wild chukars, we estimated a threshold of 1 μg/g wet weight to separate background versus elevated lead exposure for our data set. For wild chukars, we documented elevated lead exposure (ingested gizzard lead or elevated liver lead) in 5 counties and 8 mountain ranges in years 2003–2007. We estimated lead ingestion rates of 9.3% (43 of 461) using ingested gizzard lead and 8.3% (10 of 121) employing elevated liver lead (≥1 μg/g wet weight), respectively. These frequencies were respectively 1.5% and 2.5% less than the combined frequency of ingested gizzard lead and elevated liver lead (10.8%; 52 of 481). Our observed rates of elevated lead exposure were among the highest in the literature for upland birds, suggesting that chukars in northwestern Utah risk lead poisoning. These results corroborate previous findings identifying elevated lead exposure as an issue affecting non waterfowl avian species. © 2015 The Wildlife Society.